PEMBERDAYAAN KELUARGA SEBAGAI CAREGIVER DALAM MENDAMPINGI LANSIA UNTUK MENCEGAH DEPRESI - Reliani, Reliani; Prabawati, Chlara Yunita; Anandhita, Aries Chandra; Hasanah, Uswatun; Mundakir, Mundakir; Mukarromah, Nur; Husna, Anis Rosyiatul; Supatmi, Supatmi (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
The family has a very important and irreplaceable role in providing support and comprehensive care to the elderly. Empowering families as caregivers is a very important strategic step in efforts to prevent depression in the elderly. The activity took place from 13.30 to 15.00 WIB. Participants This activity was attended by 30 participants consisting of family members who have elderly people at home. The participants showed high enthusiasm during the counseling. The counseling material consisted of recognizing the signs and symptoms of depression in the elderly, the role of the family as a caregiver in accompanying the elderly, effective communication techniques with the elderly, activities that can be done with the elderly to prevent depression and How to manage stress as a caregiver. The Counseling Implementation Method was carried out using the Interactive Lecture method, Group Discussion, Demonstration and direct practice and Questions and Answers. Activity Results After attending the counseling, participants showed an increased understanding of the importance of the role of the family in preventing depression in the elderly, How to identify signs of depression in the elderly, effective communication strategies with the elderly - The right techniques for accompanying the elderly. Based on the evaluation results, 90% of participants stated that they were satisfied with the material presented and felt more prepared to carry out their role as elderly caregivers. Participants also expressed a desire to apply the knowledge gained in everyday life.